2021
DOI: 10.1002/jmv.26863
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of avidity determination in SARS‐CoV‐2 serology

Abstract: The serological responses towards severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleoprotein, receptor-binding domain (RBD), and spike protein S1 are characterized by incomplete avidity maturation. Analysis with varying concentrations of urea allows to determine distinct differences in avidity maturation, though the total process remains at an unusually low level. Despite incomplete avidity maturation, this approach allows to define early and late stages of infection. It therefore can compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 50 publications
(99 reference statements)
8
69
0
Order By: Relevance
“…So far, a number of studies evaluated the anti-Spike or anti-receptor binding domain (RBD) antibody titer [ 5 , 6 , 7 ] and their neutralizing activity [ 8 ], but little is known about the avidity of antibodies elicited by the mRNA SARS-CoV-2 vaccine [ 9 ]. Moreover, the extent of affinity maturation in COVID-19 patients and its impact on the clinical course of the disease is still a subject of active investigation [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a number of studies evaluated the anti-Spike or anti-receptor binding domain (RBD) antibody titer [ 5 , 6 , 7 ] and their neutralizing activity [ 8 ], but little is known about the avidity of antibodies elicited by the mRNA SARS-CoV-2 vaccine [ 9 ]. Moreover, the extent of affinity maturation in COVID-19 patients and its impact on the clinical course of the disease is still a subject of active investigation [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In which, the binding strength between IgG and its epitope, and strength of the multivalent interactions where both antigen interacting with multiple IgG antigen-binding sites greatly reduced [ 66 ]. Besides that, the avidity maturation of the IgG antibody allows the differentiation of acute and past SARS-CoV-2 infection, albeit not completely certain [ 73 ]. Bauer and colleagues stated that low avidity of IgG antibody illustrate an acute sars-cov-2 infection, intermediate avidity IgG might indicate recent infection and high avidity IgG might indicate a past infection [ 74 ].…”
Section: The Immune-response Towards Sars-cov-2 Infectionmentioning
confidence: 99%
“…They therefore concluded that only IgG with high affinity for the S protein can efficiently interfere with infection. 2) Recent findings show frequent incomplete avidity maturation of IgG towards SARS-CoV-2 nucleoprotein (NP), surface protein-1 (S1) and receptor-binding domain (RBD) (Strömer et al, 2020;Liu et al, 2020;Bauer et al, 2020Bauer et al, , 2021. Avidity (i. e. the strength of binding between IgG and epitope) matures in parallel to affinity.…”
mentioning
confidence: 99%
“…More than 70 percent of Covid-19 outpatients do not generate high avidity IgG at five months after the onset of disease (Bauer et al, 2020(Bauer et al, , 2021. Kinetic analysis revealed that avidity maturation stopped in parallel to the break in IgG production (Bauer et al, 2020(Bauer et al, , 2021 which seems to be leading to waning antibody levels (Seow et al, 2020). Therefore, in the majority of cases, IgG directed towards SARS-CoV-2 RBD can be predicted not to be efficient with respect to interference with the high affinity interaction between ACE2 and RBD.…”
mentioning
confidence: 99%
See 1 more Smart Citation